The Action of Certain Polyvalent Cations on the Voltage-Clamped Lobster Axon - Blaustein, M. P. (The Rockefeller University Press, 1968)
Calcium appears to be an essential participant in axon excitation processes. Many other polyvalent metal ions have calcium-like actions on axons. We have used the voltage-clamped lobster giant axon to test the effect of several of these cations on the position of the peak initial (sodium) and steady-state (potassium) conductance vs. voltage curves on the voltage axis as well as on the rate parameters for excitation processes. Among the alkaline earth metals, Mg(+2) is a very poor substitute for Ca(+2), while Ba(+2) behaves like "high calcium" when substituted for Ca(+2) on a mole-for-mole basis. The transition metal ions, Ni(+2), Co(+2), and Cd(+2) also act like high calcium when substituted mole-for-mole. Among the trivalent ions, La(+3) is a very effective Ca(+2) replacement. Al(+3) and Fe(+3) are extremely active and seem to have some similar effects. Al(+3) is effective at concentrations as low as 10(-5) M. The data suggest that many of these ions may interact with the same cation-binding sites on the axon membrane, and that the relative effects on the membrane conductance and rate parameters depend on the relative binding constants of the ions. The total amount of Na(+) transferred during a large depolarizing transient is nearly independent of the kind or amount of polyvalent ion applied.